STRAWBERRY DISTRIBUTION IN CIWIDEY: AN ANALYSIS OF VALUE CHAIN AND PRICE DISPARITY - Dewi, Nurlaela Kumala; Arffien, Afferdhy; Nurhayana, Hafiz Fauzan; Saefudin, Arif (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
Strawberries, which are closely associated with the Ciwidey District in West Java, pass through a supply chain that includes numerous stakeholders, from farmers to retailers. This complex chain results in significant price disparities and lowers farmers' profits. This study aims to analyse the value chain and price disparity of strawberry commodities in Ciwidey District, Bandung Regency, West Java. The value chain analysis method is used to understand and improve the way a product or service generates value, and Hayami's analysis is used to calculate the added value for each actor in this supply chain. Based on the results of the analysis, the value chain of strawberry commodities in Ciwidey District obtained parties/actors that play a role in this supply chain, such as farmers, who act as producers of the strawberry cultivation process. Small collectors who collect the strawberry harvest directly from the farmers do the sorting and grading and sell it to large collectors. Large collectors act as traders who collect the strawberry harvest and distribute the sales more widely. Retailers act as traders who sell strawberries to consumers. The added value obtained by farmers is Rp 300.01/kg, small collectors Rp 6,345.67/kg, large collectors Rp 14,799.29/kg, and retailers Rp 18,224.8/kg. In this strawberry commodity value chain, the disparity value from the farmer to the consumer level is Rp 63,550/kg. The implications of this study provide insight into market dynamics and offer a basis for improvements and interventions that can help all parties, especially in improving the economic conditions of farmers. The strawberry supply chain's complexity impacts various actors differently. Farmers suffer reduced profits due to price disparities, while retailers gain from price markups. Consumers experience price variability. This study highlights the need for interventions to streamline the supply chain, reduce intermediaries, and improve farmers' economic conditions.